Peningkatan Keterampilan Berpikir Kritis Mahasiswa Melalui Penerapan Model Pembelajaran Learning Cycle 7e Berbasis Lesson Study - Nur Amaliah; Fitri Ningsih; Sri Endah Indriwati; Abdul Gofur (Universitas Sulawesi Barat, 2020)
Learning aimed to help students undergo the learning process so that effective learning behavior was realized. Effective learning was learning that can produced useful learning and student centered learning. In reality, students in class were still passive, have not been able to expressed their opinion, and were less active in constructing their own knowledge. This showed that learning objectives have not been achieved according to the sixth level of KKNI’s standard. Therefore, this study was conducted using a learning cycle 7E learning model based on lesson study to improve student’s critical thinking skills. The result showed that there had been an increase in student’s critical thinking skills during learning with four lesson study. The improvement of critical thinking skills on the interpretation indicator was 0.03%, inference was 0.03%, analysis was 0.06%, evaluation was 0.28%, explanations were 0.66%, and self-regulation was 0.91%.